(untitled) (Patan Prospective Journal, 2024)
This paper has delved into the conceptual clarity of literature review, its elements, the reasons for writing literature, the structural foundation, and challenges that researchers undergo when preparing to write the review of literature. The article has aimed to educate the readers about the methods of writing literature review for academic purpose. The major exploration is the researchers without being aware of the authenticity, credibility, and currency of the materials cannot help to be up to date with the existing significant development in the field of the study. Their primary task is to gather relevant and reliable information on the topic before beginning to write the literature review so that they can fit it in their dissertation. The article has employed the qualitative research design with the focus on the secondary data on the literature review. The university students can benefit from this article a lot when they commence to write the literature review for their dissertations or theses as the partial requirements of their academic degrees.